Dangers of Free Sex Lurking Adolescent in Jayawaras Village, Garut - Nina Sumarni; Udin Rosidin; Umar Sumarna; Iwan Sholahudin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Sexual behavior carried out before marriage can be at risk of sexually transmitted diseases and unwanted teenage pregnancy, which can lead to abortion and marriage at a young age. The incidence of free sex in adolescents is caused by adolescents who do not understand the impact of free sex on their health and life, lack of guidance from their families, and poor friendships. Another impact of premarital sexual behavior is the risk of being infected with HIV. The purpose of the activity was to increase knowledge and understanding of the dangers of free sex for adolescent. The method used was lecture method via zoom, poster installation, question and answer and group discussion. Result of health education activities in RW 03 and RW 13 Jayawaras Village, Tarogong Kidul Regency which was held on Thursday, September 29, 2021 Time : 13.00 - finished. Furthermore, the installation of educational posters in RW 03 and RW 14. In the process of implementing counseling; The participants participated in the counseling enthusiastically and the counseling was carried out using online method. The outreach activities were conducive because the community paid attention to the material presented well.